REFINING ORGANISATIONAL COMMITMENT AND EFFECTIVENESS THROUGH THE JOHARI WINDOW MODEL: A CONCEPTUAL REVIEW - Ajayi Olalekan Ezekiel; Kamoru Lanre Akanbi; Muhammad Taofeek Olowookere; Ajirowo Wasiu Olumuyiwa (Sampoerna University, 2026)
Organizations are increasingly challenged with promoting employee commitment and sustainable effectiveness due to poor communication, low interpersonal trust, and deficient employee self-awareness. These issues are usually exacerbated with a rigid organizational culture that stifles openness and constructive feedback. This conceptual paper discusses the Johari Window model as a strategic instrument for solving these organizational challenges. The study, based on a broad spectrum of recent research, discusses how self-awareness, feedback mechanisms, and interpersonal dynamics, fundamental pillars of the Johari Window, would affect human resources management. The research based on the review indicates that the Johari Window ensures employee commitment by enhancing self-awareness and formal feedback, which deepens affective and normative organizational bonds. The model also ensures organizational effectiveness by enhancing interpersonal trust and improving communication, collaboration, and team cohesion. It also has practical applications for HR practices, for example, onboarding, leadership development, and performance management. The research concluded that implementing the Johari Window within organizational culture greatly improves employee engagement and organizational performance. It thus recommends that organizations embed feedback culture, embed the model in leadership development, and create psychological safety for long-term success.